The Influence of Agrarian Reform, Social Capital, Farmer Spirituality and Personal Tribute on Farmers' Welfare in Kabupaten Bogor, West Java - Samudra Ivan Supratikno; Isbandi Rukminto Adi; Djuara P. Lubis (Eduvest - Journal of Universal Studies, 2023)
Residents in various villages to have agricultural land. The distribution of soil types in the agrarian reform program in Kabupaten Bogor is divided into two categories, namely paddy fields and dry land. The number of family members beneficiaries of agrarian reform has an average of around 3-4 people with a standard deviation of 1.3. Agricultural land ownership status affects the welfare of farmers. Social capital is related to cooperation in a society to achieve a better quality of life supported by values ​​and norms as the main elements including trust, reciprocity and collective rules. The influence of spirituality on the welfare of farmers in Bogor Regency is very important to have. Some farmers think that having a high level of education is not important to work as a farmer. Personal attributes influence the welfare of farmers in Bogor Regency. The main objective of this study was to determine the effect of the agrarian reform program, social capital, farmer spirituality and personal attributes on the welfare of farmers in Kabupaten Bogor, West Java. This study was designed using a descriptive method with a quantitative approach. Moreover, To find out how much influence these personal attributes have, this study uses 5 (five) conceptual points in the hypothesis. The five points that influence personal attributes include extraversion, agreeableness, conscientiousness, neuroticism and openness. Most of the farmers feel less confident in carrying out their agricultural tasks, but they have good communication skills and are full of enthusiasm.